LATIHAN AKTIFITAS FISIK : RANGE OF MOTION UNTUK MENGURANGI NYERI SENDI PADA LANSIA DI DESA POHGADING TIMUR KABUPATEN LOMBOK TIMUR - Maruli Taufandas (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2021)
The purpose of this community service based activity aims to provide insight into knowledge and understanding of the community in East Pohgading Village about range of motion. The target of community service is the elderly in East Pohgading Village. Physical activity exercise in the form of range of motion has never been done by the elderly. The problem is solved by three stages of activities, namely: preparation, implementation, and evaluation. The preparation stage starts from the preparation of proposals, coordination with partners, preparation of tools and materials, and publication of invitations. Implementation is done by examining the joint pain scale in the elderly and carrying out physical activity exercises with the elderly. The evaluation was carried out with a pre-post test of range of motion activities as much as 70% of the total targets to determine the success of community service activities. The results of community service activities show the level of success with an indication of the suitability between physical activity exercises in the form of range of motion with the needs of the elderly in East Pohgading Village. This exercise is useful for the daily activities of the elderly in light activities and does not require a lot of energy.